Effect of in vitro Digestion on the Bioaccessibility of Polyphenols and Potential Prebiotic Properties of Potato Peel - Mall, Urvashi P.; Patel, Vinayak H. (Recent Advances in Food Nutrition & Agriculture, 2024)
BackgroundPotato peel is a byproduct of the potato processing industry and a potential source of functional ingredients such as dietary fiber, polyphenols, and prebiotics. However, the bioaccessibility of polyphenols and antioxidants during in vitro digestion as well as prebiotic potential after in vitro digestion of potato peel flour has not been reported.ObjectiveThe study was designed to assess the bioaccessibility of polyphenols and the prebiotic potential of potato peel flour.MethodsIn this study, the changes in polyphenol content and antioxidant capacity during different phases of in vitro digestion, including salivary, gastric and intestinal phases were studied. Additionally, an investigation was conducted to evaluate the prebiotic properties of potato peel flour by in vitro fermentation with Lactobacillus acidophilus.ResultsThe findings revealed a significant increase in the recovery index for total phenolic content during both gastric (106.90%) and intestinal (102.71%) digestive phases. Furthermore, polyphenols in potato peel flour exhibited high residual intestinal digestibility index values (>90%). The antioxidant capacity increased by >50% during various phases of in vitro digestion. Regarding prebiotic properties, potato peel flour significantly increased L. acidophilus counts and promoted the production of short-chain fatty acids, specifically propionate and butyrate.ConclusionThis study suggests that potato peel flour has the potential to serve as a functional ingredient or nutraceutical that can enhance health and may help in reducing environmental problems.
Keywords: in vitro